2019
DOI: 10.1007/s13592-019-00707-7
|View full text |Cite
|
Sign up to set email alerts
|

Trialling techniques for rearing long-tongued bumblebees under laboratory conditions

Abstract: Bumblebees are important pollinating insects, but many species have suffered declines over the last century. Long-tongued bumblebees have been identified as particularly at risk, partly due to their more selective diet. Attempts to study these species in captivity have been impeded by stress-induced behaviours which cause queens to kill or abandon their brood. Here, we attempt to further develop techniques, using queen pairing and Bombus terrestris cocoons, to successfully rear two common long-tongued bumblebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(44 reference statements)
0
10
1
Order By: Relevance
“…Because both of these species are pocket makers and we are still in the early days of rearing optimisation, it is important not to discount the effects of queen behaviour on colony success. In personal observations of the queens here and in our previous work, we found B. hortorum queens to be much more sensitive to physical disturbances (Carnell et al 2020). Although this does not explain our findings here, decades of rearing work on a variety of species has clearly demonstrated that bumblebee species vary widely in their performance under captive conditions, across and within the pocket maker and pollen storer groups (Fandiño 2007;Ptáček et al 2015;Sheikh 2016;Velthuis and Van Doorn 2006).…”
Section: Discussioncontrasting
confidence: 42%
See 4 more Smart Citations
“…Because both of these species are pocket makers and we are still in the early days of rearing optimisation, it is important not to discount the effects of queen behaviour on colony success. In personal observations of the queens here and in our previous work, we found B. hortorum queens to be much more sensitive to physical disturbances (Carnell et al 2020). Although this does not explain our findings here, decades of rearing work on a variety of species has clearly demonstrated that bumblebee species vary widely in their performance under captive conditions, across and within the pocket maker and pollen storer groups (Fandiño 2007;Ptáček et al 2015;Sheikh 2016;Velthuis and Van Doorn 2006).…”
Section: Discussioncontrasting
confidence: 42%
“…We found that queens of B. pascuorum and B. hortorum can survive and successfully rear workers on both the less diverse hawthorn pollen and the more diverse wildflower mix and that a less diverse pollen mix can be as good as a more diverse one. A wax moth infestation developed towards the end of the experiment, but despite this, and the additional stress it may have imposed on queens, the proportion of queens that laid eggs was amongst the highest observed in these species when reared in captivity (Bučánková et al 2012;Ptáček et al 2015;Carnell et al 2020). Very few workers are required for queens to switch to male production (Carnell et al 2020), so it is quite likely that in the absence of wax moths this would have occurred.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations